2013
DOI: 10.1097/mpa.0b013e3182554d8e
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Saizen in Combination With Stilamin on Intestinal Mucosa of a Rabbit Model of Severe Acute Pancreatitis

Abstract: The combination of saizen with stilamin can enhance intestinal mucosa barrier function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…According to the current literature, neuropeptide receptors and the potential clinical relevance of the ligand SST 28 Neurogenic inflammation in rats, inhibits proliferation, chemotaxis, cytokine and immunoglobulin secretion of lymphocytes, monocytes and macrophages, murine EAE, rabbit acute pancreatitis [127,[132][133][134][135]147] sst2 sst3 sst5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the current literature, neuropeptide receptors and the potential clinical relevance of the ligand SST 28 Neurogenic inflammation in rats, inhibits proliferation, chemotaxis, cytokine and immunoglobulin secretion of lymphocytes, monocytes and macrophages, murine EAE, rabbit acute pancreatitis [127,[132][133][134][135]147] sst2 sst3 sst5…”
Section: Discussionmentioning
confidence: 99%
“…Octreotide was shown to inhibit cerulein‐induced acute murine pancreatitis. Somatostatin was also reported to relieve rabbit pancreatitis in combination with growth hormone .…”
Section: Anti‐inflammatory Neuropeptidesmentioning
confidence: 99%
“…There is overwhelming evidence that SAP is combined with different degree of multiple organ dysfunction syndrome. 22 , 23 Moreover, some clinical and experimental studies 24 , 25 have shown that intestinal mucosa injury is a critical part in the progression of SAP. Consistently, in this study, we find that the villous height, crypt depth and mucosal thickness of small intestine tissue in SAP group gradually decrease along with the disease progression.…”
Section: Discussionmentioning
confidence: 99%